Similarity and the coordination of ownership - Grüning, David; Krueger, Joachim I. (Behavioral and brain sciences, 2023)
We discuss and expand Boyer's idea of ownership coordination. Interpersonal similarity, we suggest, can moderate the attainment of coordination: Perceived similarity predicts coordination costs, whereas actual similarity dictates coordination success and the severity of illusory assumptions regarding a shared understanding of ownership. The example of similarity highlights the complexity of the social projection process uncritically assumed behind ownership coordination.